Kedudukan Al-Qur’an dan Sunnah dalam penelitian ekonomi dan bisnis syariah - Afani, Moh. (Maliki Interdisciplinary Journal, 2024)
The Quran and Sunnah are the main sources of Islamic law which regulate all aspects of people's lives, including economic aspects. The Qur'an and Sunnah regulate the field of Islamic economics in detail. This research aims to determine the role of the Al-Qur'an and Sunnah in sharia economic research. The method used in this writing is library research. The data in this research was obtained through the use of documentary methods sourced from journal articles. The results of this research show that the Al-Qur'an is positioned as the main guide in sharia economic research, while the Sunnah/Hadith is positioned as the second rule which is used as an explanation of the Al-Qur'an.